RISK MITIGATION AS A MEDIATING FACTOR IN THE RELATIONSHIP BETWEEN TOP MANAGEMENT SUPPORT AND CONSTRUCTION PROJECT PERFORMANCE: - - Astana, I Nyoman Yudha; Aribudiman, I Nyoman; Widajaya, Anak Agung Ngurah Agung Aditya (Journal of Applied Engineering Science, 2024)
Construction projects are complex and high-risk activities. Project risks can come from various factors, such as technical, environmental, social, and economic factors. Top management support and project risk mitigation are critical factors influencing construction project performance. This research analyzes the influence of top management support and project risk mitigation on construction project performance. This research method uses a quantitative statistical approach based on primary data collected through questionnaires distributed to 50 construction companies in Bali Province, randomly selected from the population of construction companies that comprise large, medium, and small qualifications. Secondary data was obtained through a relevant literature review, which includes three variables, i.e., top management support, project risk mitigation, and construction project performance. The research shows that top management support and project risk mitigation significantly influence construction project performance. Top management support increases worker motivation and productivity, efficiency, work effectiveness, and work quality and safety in construction projects. Meanwhile, risk mitigation improves projects through control, time estimation, information presentation, worker motivation, technology, and resources. In addition, project risk mitigation is a mediating variable in the relationship between top management support and construction project performance.
Keywords: top management support, project risk mitigation, construction project performance